Vitamin E (Alpha Tocopherol) Level in the Dorsal Skin of Sunda Porcupine (Hystrix javanica) - Prawira, Andhika Yudha; Farida, Wartika Rosa; Darusman, Huda Salahudin; Novelina, Savitri; Agungpriyono, Srihadi (Jurnal Riset Veteriner Indonesia (Journal of The Indonesian Veterinary Research), 2018)
Alpha tocopherol, as the most active component of Vitamine E, is identified as antioxidant present in some parts of the skin and the concentration is vary in several regions of the body due to the skin characteristic of the region. Sunda porcupine (Hystrix javanica) is one of the rodents in Indonesia with quill as its spesific skin characteristic. The porcupine quill are distributed in various shapes and sizes in body parts, while dorsal regions and the tail is the body part that has the most developed quill form. This study aimed to measure alpha tocopherol content in the dorsal region skin of male and female Sunda porcupine. The study used skin samples of thoracodorsal and lumbosacral regions of 6 adult Sunda porcupine (3 males and 3 females) and 2 frozen specimens (1 male and 1 female). Samples were prepared and processed for analysis through high performance liquid chromatography. The results showed that the level of tocopherol in the dorsal thoracic region of males and females was much higher than that of the lumbosacral region. The results of this study indicate the characteristics of the skin region affect the levels of alpha tocopherol in the region.